2020
DOI: 10.3390/microorganisms8040525
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Infection Suppresses CD34+ Progenitor Cell Engraftment in Humanized Mice

Abstract: Human cytomegalovirus (HCMV) infection is a serious complication in hematopoietic stem cell transplant (HSCT) recipients due to virus-induced myelosuppression and impairment of stem cell engraftment. Despite the clear clinical link between myelosuppression and HCMV infection, little is known about the mechanism(s) by which the virus inhibits normal hematopoiesis because of the strict species specificity and the lack of surrogate animal models. In this study, we developed a novel humanized mouse model system th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…We hypothesize that the virus had an important role in the engraftment delay in our cohort, as the adjusted model maintained the signi cance of pre-engraftment csCMVi as a risk factor, and CMV is a well-known myelotoxic pathogen. (21,22) Cytomegalovirus replication is a possible contributor to acute GVHD development, as demonstrated by Cantoni et al (23) In our series, the frequency of aGVHD was not different in pre-and postengraftment events.…”
Section: Discussionsupporting
confidence: 65%
“…We hypothesize that the virus had an important role in the engraftment delay in our cohort, as the adjusted model maintained the signi cance of pre-engraftment csCMVi as a risk factor, and CMV is a well-known myelotoxic pathogen. (21,22) Cytomegalovirus replication is a possible contributor to acute GVHD development, as demonstrated by Cantoni et al (23) In our series, the frequency of aGVHD was not different in pre-and postengraftment events.…”
Section: Discussionsupporting
confidence: 65%
“…In parallel, direct infection of monocytes promotes differentiation towards macrophages ( Ibanez et al., 1991 ; Soderberg-Naucler et al., 2001 ; Smith et al., 2004 ; Chan et al., 2012b ) and while the specific role of monocytes are outside the scope of this review, they are discussed recently elsewhere [reviewed in ( Min et al., 2020 )]. We have also previously shown that infection of HPCs specifically alters differentiation both in vitro and in vivo ( Crawford et al., 2018 ; Crawford et al., 2019 ; Crawford et al., 2020 ), highlighting the cell type-specific interactions between the virus and host, particularly as related to cellular differentiation. In short, HPCs provide the latent reservoir, monocytes disseminate the virus, and macrophages produce infectious virus for spread; and the cellular differentiation state and cellular heterogeneity play critical roles in this balance.…”
Section: Betaherpesvirus Latency and Hematopoiesismentioning
confidence: 84%
“…In addition, in murine CMV bone marrow engraftment models, infection is also associated with cytokine dysregulation ( Steffens et al., 1998 ). Further, engraftment of humanized mice with a pool of HPCs wherein only a subset are HCMV-infected is sufficient to result in engraftment delay and suppression ( Crawford et al., 2020 ), which is comparable to clinical patients who receive a seropositive, but undetectable viral load, bone marrow transplant.…”
Section: Betaherpesvirus Latency and Hematopoiesismentioning
confidence: 99%
“…Deletion of Rat CMV R33 reduced vascular sclerosis and increased time to chronic rejection in a rat model of heart transplantation, and deletion of MCMV M33 reduced cardiac allograft vasculopathy in a mouse model of aortic transplantation (Streblow et al, 2005;Fritz et al, 2018). These animal models continue to be developed, including the generation of a humanized mice model, which may soon lead to further exciting insight about the roles of individual viral genes in post-transplant cytomegalovirus disease (Streblow et al, 2015;Crawford et al, 2020;Gezinir et al, 2020;Holtappels et al, 2020;Shah et al, 2020). However, the species-specific nature of herpesviruses will continue to create challenges in understanding how vGPCRs function in vivo.…”
Section: Post-transplant Diseasementioning
confidence: 99%